2022
DOI: 10.1364/boe.481248
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional image-guided topical photodynamic therapy system with light dosimetry dynamic planning and monitoring

Abstract: Photodynamic therapy (PDT) has shown significant potential for skin disease treatment. As a key element, light is critical to influencing its treatment outcome, and light dosimetry is an issue of much concern for researchers. However, because of three-dimensional irregularity in shape and patient’s movement during the therapy, irradiance hardly keeps uniform on the lesion and flux measurement remains a challenge. In this work, we report the development of a three-dimensional image-guided PDT system, and the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It is well established that tumors exhibit considerable heterogeneity, which may impede the efficacy of photodynamic diagnostics and therapy, especially in deep-seated tumors. One potential solution to this issue may be the preliminary prediction of light propagation throughout the entire tumor volume for different irradiation geometries and for different configurations of light-scattering fibers [60]. The utilization of a three-dimensional tumor model, previously obtained through computed tomography or magnetic resonance imaging (MRI) with Monte Carlo simulation, permits the simulation of PDT within the tumor volume [104], and the walls of hollow organs [100,106].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that tumors exhibit considerable heterogeneity, which may impede the efficacy of photodynamic diagnostics and therapy, especially in deep-seated tumors. One potential solution to this issue may be the preliminary prediction of light propagation throughout the entire tumor volume for different irradiation geometries and for different configurations of light-scattering fibers [60]. The utilization of a three-dimensional tumor model, previously obtained through computed tomography or magnetic resonance imaging (MRI) with Monte Carlo simulation, permits the simulation of PDT within the tumor volume [104], and the walls of hollow organs [100,106].…”
Section: Discussionmentioning
confidence: 99%
“…This can result in disparate treatment efficacy. The PDT of tumors was controlled using 3D image analysis and dynamic irradiation planning, as well as monitoring of light flux density when targeting heterogeneous 3D lesions by controlling the brightness of the LED array [59,60]. The findings indicated that the adjusted model of tumor illumination by an LED matrix with optimal brightness distribution according to the size and shape of the lesion enhances the uniformity of tissue irradiation and the efficacy of therapy, even when the patient moves during PDT.…”
Section: Fluorescence Imagingmentioning
confidence: 99%
See 1 more Smart Citation